Perancangan Standar Operasional Prosedur (SOP) dan Pedoman Akuntansi Pengelolaan Kas pada Raudhatul Athfal Nurul Amal Bekasi Timur - Nazila Alvi Ramadhani; Ayatulloh Michael Musyaffi; Aji Ahmadi Sasmi (LPPM Universitas Negeri Jakarta, 2026)
This study aims to design Standard Operating Procedures (SOP) and accounting guidelines for cash management at Raudhatul Athfal Nurul Amal Bekasi Timur. The study addresses problems related to cash management, including manual cash recording, unorganized transaction documentation, and the absence of written procedures for cash receipts and disbursements. This research employed a Research and Development (R&D) method using the ADDIE model, limited to the analysis, design, and development stages. Data were collected through interviews, observations, and documentation involving school management personnel. The analysis stage utilized the PIECES framework to identify institutional needs and problems. The study resulted in two products: a cash management SOP and accounting guidelines. The SOP provides procedures for cash receipts and disbursements, while the accounting guidelines include account classifications, journal illustrations, and Excel-based recording formats. The products were considered useful and appropriate for supporting more structured and accountable cash management activities.